2013
DOI: 10.1177/0954409712473095
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of noise sources in high-speed trains

Abstract: In this paper, the quantification of the external noise sources in high-speed trains is discussed. A thorough understanding of the underlying causes of noise generation in high-speed trains is needed to develop effective noise control measures. However, because high-speed trains produce a complex array of sounds, it is very difficult to determine each individual source of noise. In this study, the delay-and-sum beamforming method, which uses microphone arrays, was used to separate the noise sources and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Martens et al [21] used a spiral array with a diameter of 4 m in order to improve the resolution at low frequencies but they also used a spiral array with 2 m diameter and smaller distance between microphones to operate up to 5 kHz. The array configuration used by Noh et al [24] was radial and irregular with nested arrays using 96 microphones and obtaining good resolution in the range between 200 and 8000 Hz.…”
Section: Microphone Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Martens et al [21] used a spiral array with a diameter of 4 m in order to improve the resolution at low frequencies but they also used a spiral array with 2 m diameter and smaller distance between microphones to operate up to 5 kHz. The array configuration used by Noh et al [24] was radial and irregular with nested arrays using 96 microphones and obtaining good resolution in the range between 200 and 8000 Hz.…”
Section: Microphone Arraysmentioning
confidence: 99%
“…However, to prevent spatial aliasing the distance between microphones should be less than half the acoustic wavelength which limits the upper frequency that can be resolved [15]. Examples of measurements using microphone arrays during the passage of different high-speed trains are given in References [17][18][19][20][21][22][23][24]. Different configurations of microphone array can be used in order to optimise its performance depending on the situation.…”
Section: Microphone Arraysmentioning
confidence: 99%
“…Several experimental and numerical studies have been performed to study the flow and acoustic features of the pantograph recess [12,13]. Noh et al [12] carried out noise tests for a full-scale Korean high-speed train (KTX). They found that the noise from the recess was at similar level to that from the pantograph at a speed of 300 km/h.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the noise produced by high-speed trains is becoming increasingly significant and it has a great influence on surrounding environment and ride comfort. According to some studies [1][2], the noise can be mainly divided into rolling noise, traction noise and aerodynamic noise. Moreover, the aerodynamic noise is strongly dependent on the train speed U, being approximately proportional to U 6 -U 8 .…”
Section: Introductionmentioning
confidence: 99%